KS-Detect - Validation of Solar Thermal PCR for the Diagnosis of Kaposi's Sarcoma Using Pseudo-Biopsy Samples. - Ryan Snodgrass; Andrea Gardner; Li Jiang; Cheng Fu; Ethel Cesarman; David Erickson (PLoS ONE, 2016)
Resource-limited settings present unique engineering challenges for medical diagnostics. Diagnosis is often needed for those unable to reach central healthcare systems, making portability and independence from traditional energy infrastructure essential device parameters. In 2014, our group presented a microfluidic device that performed a solar-powered variant of the polymerase chain reaction, which we called solar thermal PCR. In this work, we expand on our previous effort by presenting an integrated, portable, solar thermal PCR system targeted towards the diagnosis of Kaposi's sarcoma. We call this system KS-Detect, and we now report the system's performance as a diagnostic tool using pseudo-biopsy samples made from varying concentrations of human lymphoma cell lines positive for the KS herpesvirus (KSHV). KS-Detect achieved 83% sensitivity and 70% specificity at high (≥ 10%) KSHV+ cell concentrations when diagnosing pseudo-biopsy samples by smartphone image. Using histology, we confirm that our prepared pseudo-biopsies contain similar KSHV+ cell concentrations as human biopsies positive for KS. Through our testing of samples derived from human cell lines, we validate KS-Detect as a viable, portable KS diagnostic tool, and we identify critical engineering considerations for future solar-thermal PCR devices.